BOOK REVIEW. ORAL TRADITION OF PATU MBOJO - Ni Made Ary Widiastini (Humaniora, 2015)
This book explains in details an oral tradition of a society in West Nusa Tenggara. The oral tradition belongs to the culture of Bima ethnic society. This book is a Ph.D. dissertation, which was written by the late Ahmad Badrun from the Faculty of Cultural and Knowledge, Universitas Indonesia. This book is worth reading by academicians (both university students and lecturers), especially for those who are doing their research on oral tradition. This book follows the Ph. D dissertation format and consists of nine chapters as follows: (1) Chapter I is the Introduction, (2) Chapter II is the Theoretical Framework, (3) Chapter III is the Research Method, and (4) Chapters IV, V, VI, VII, and VIII are he result and discussion which are adjusted to the formulated problems or questions and have already been mentioned in Chapter I, (5) Chapter IX is the Conclusion. Therefore, this book can be used as an example for writing and doing any kind of research.